TEACHER TRANSLANGUAGING STRATEGIES IN TEACHING PRONUNCIATION AT SMA NEGERI 1 PERCUT SEI TUAN - Gloria Pasca Simarmata; Ameera Fadhillah; Priska Oktaviani Br Ginting (CV. Adiba Aisha Amira, 2026)
This study is based on the importance of mastering pronunciation to support students’ reading skills in EFL contexts, as well as the role of translanguaging strategies in helping students’ understanding. The aim of this study is to analyze the implementation of translanguaging strategies used by a teacher in teaching pronunciation at SMA Negeri 1 Percut Sei Tuan. This study uses a descriptive qualitative design, with one English teacher as the subject, and the data were collected through interviews. The data were analyzed using an interactive model, including data reduction, data display, and conclusion drawing. The findings show that the teacher applied two main translanguaging strategies, namely translation and L1 scaffolding. Translation was found to be the most dominant strategy, while L1 scaffolding was used to support students in understanding concepts, materials, and the pronunciation of English words. These strategies help students understand the material better, reduce ambiguity in meaning, and improve the effectiveness of pronunciation learning during reading activities. The findings imply that the strategic use of translanguaging can be an effective approach in teaching pronunciation for EFL students.